Motorcycle Engine Start System Using Fingerprint and Voice Command - Wabdillah; Akbar Iskandar; Syahriandi (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
This study aims to design and implement an engine start system using fingerprints and voice commands to turn on and turn off Arduino-based motorcycle controlled using an Android smartphone. This engine start system is designed using Arduino Uno as the main part which is then assembled with devices such as the HC-05 Bluetooth module to connect the Android application with the microcontroller on the motorbike, the FP10MA fingerprint, relay and speaker which are installed on the motorbike's electrical parts. Making the starter engine system on this motorbike is to make it easier for users to turn on the motorbike without using a key so that they only use voice commands through an application found on an Android smartphone. In the security section, fingerprints are used as a substitute for manual ignition on motorbikes. The results of a series of engine start system tests show that the engine start security system using a fringerprint only takes 2 seconds to start the engine and 3 seconds by using a voice command via bluetooth HC-05 and is able to start from a distance of 16 meters which is controlled via a smartphone.